2002
DOI: 10.1046/j.1570-7458.2002.00954.x
|View full text |Cite
|
Sign up to set email alerts
|

Behavioural plasticity in support of a benefit for aggregation pheromone use in Drosophila melanogaster

Abstract: We explored behavioural plasticity in the use of aggregation pheromone in the fruit fly Drosophila melanogaster Meigen (Diptera: Drosophilidae). Based on previous field observations, we formulated two hypotheses on a benefit of using aggregation pheromone for aggregated oviposition. One hypothesis concerns a benefit to the females themselves, where reduced harassment by males can enhance oviposition rate; the other concerns a benefit to their offspring, where larvae can exploit arduous substrates more efficien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
94
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(97 citation statements)
references
References 51 publications
3
94
0
Order By: Relevance
“…cuticular hydrocarbons that induce attraction between individuals [22,23]. Chemical communication is also widespread in drosophilid behaviour, including those associated with spatial aggregation in adult flies [24-26]. Because several receptors on the cephalic lobe of Drosophila larvae have gustatory, mechanosensory and olfactory functions [27], both chemical and physical cues (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…cuticular hydrocarbons that induce attraction between individuals [22,23]. Chemical communication is also widespread in drosophilid behaviour, including those associated with spatial aggregation in adult flies [24-26]. Because several receptors on the cephalic lobe of Drosophila larvae have gustatory, mechanosensory and olfactory functions [27], both chemical and physical cues (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Wertheim et al (2002b) have shown that the component Allee effect found in their study was caused by the presence of several females that visited a patch. Thus, the benefits that accrue from selecting resource patches that already contain conspecifics (Wertheim et al 2002a) vary with the patch characteristics (substrate features) and the density of conspecifics.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, cVA also has a non-sex specific function; in the presence of food, cVA promotes aggregation of both males and females (Bartelt et al, 1985;Wertheim et al, 2002;Xu et al, 2005;Lebreton et al, 2014). Again, prior experience of exposure to cVA has an effect in the context of aggregation.…”
Section: A Second Pheromonal System: Cis-vaccenyl Acetatementioning
confidence: 99%
“…Detection of the same pheromone by both the olfactory and taste systems may increase the range of functions of a single compound. For instance, at longer range the smell of cVA combined with the smell of food triggers attraction to food substrate already occupied by flies (Bartelt et al, 1985;Wertheim et al, 2002;Lebreton et al, 2012). In the meantime, the taste system would not be able to detect low concentrations of cVA at such a long distance.…”
Section: Pheromone Processing In Drosophilamentioning
confidence: 99%